Enhancing Charge Carrier Lifetime in Metal Oxide Photoelectrodes through Mild Hydrogen Treatment. Issue 22 (25th August 2017) - Jang, Ji‐Wook; Friedrich, Dennis; Müller, Sönke; Lamers, Marlene; Hempel, Hannes; Lardhi, Sheikha; Cao, Zhen; Harb, Moussab; Cavallo, Luigi; Heller, René; Eichberger, Rainer; van de Krol, Roel; et al.
Abstract: Widespread application of solar water splitting for energy conversion is largely dependent on the progress in developing not only efficient but also cheap and scalable photoelectrodes. Metal oxides, which can be deposited with scalable techniques and are relatively cheap, are particularly interesting, but high efficiency is still hindered by the poor carrier transport properties (i.e., carrier mobility and lifetime). Here, a mild hydrogen treatment is introduced to bismuth vanadate (BiVO4 ), which is one of the most promising metal oxide photoelectrodes, as a method to overcome the carrier transport limitations. Time‐resolved microwave and terahertz conductivity measurements reveal more than twofold enhancement of the carrier lifetime for the hydrogen‐treated BiVO4, without significantly affecting the carrier mobility. This is in contrast to the case of tungsten‐doped BiVO4, although hydrogen is also a donor type dopant in BiVO4 . The enhancement in carrier lifetime is found to be caused by significant reduction of trap‐assisted recombination, either via passivation or reduction of deep trap states related to vanadium antisite on bismuth or vanadium interstitials according to density functional theory calculations. Overall, these findings provide further insights on the interplay between defect modulation and carrier transport in metal oxides, which benefit the development of low‐cost, highly‐efficient solar energy conversion devices. Abstract : Overcoming poor charge carrier transport represents one of the biggest challenges in the development of metal oxide photoelectrodes . Time‐resolved conductivity measurements and density functional theory calculations reveal that a simple postsynthesis hydrogen treatment at 300 °C reduces the number of deep trap states in metal oxides. As a result, the charge carrier lifetime and overall photoelectrochemical performance are significantly enhanced.